2015
DOI: 10.1016/j.biotechadv.2015.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and challenges in three-dimensional brown adipogenesis of stem cells

Abstract: The formation of brown adipose tissue (BAT) via brown adipogenesis has become a notable process due to its ability to expend energy as heat with implications in the treatment of metabolic disorders and obesity. With the advent of complexity within white adipose tissue (WAT) along with inducible brown adipocytes (also known as brite and beige), there has been a surge in deciphering adipocyte biology as well as in vivo adipogenic microenvironments. A therapeutic outcome would benefit from understanding early eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 297 publications
(338 reference statements)
0
23
0
Order By: Relevance
“…Consistent with previous studies suggesting several cell types and tissue structures to be involved in native browning 59 , we observed that, beyond adipocytes, vessel-like structures appeared to remain viable during ex vivo culture and that tissue fragments became re-vascularized after re-implantation. While further studies are needed to delineate the molecular pathways governing the BAT transplants, the ability to culture large quantities of tissue at once while retaining 3D structure, including vascular cells and structures, holds translational clinical utility, and has typically not been possible through the culture of isolated adipocyte progenitor cells 60 , 61 .…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous studies suggesting several cell types and tissue structures to be involved in native browning 59 , we observed that, beyond adipocytes, vessel-like structures appeared to remain viable during ex vivo culture and that tissue fragments became re-vascularized after re-implantation. While further studies are needed to delineate the molecular pathways governing the BAT transplants, the ability to culture large quantities of tissue at once while retaining 3D structure, including vascular cells and structures, holds translational clinical utility, and has typically not been possible through the culture of isolated adipocyte progenitor cells 60 , 61 .…”
Section: Discussionmentioning
confidence: 99%
“…The process of adipocyte differentiation from preadipocytes has been extensively studied in vitro using two‐dimensional models and, more recently, coculture models to examine the effects of one cell type on the differentiation of preadipocytes in vitro . Studies have begun to shed light on in vivo adipocyte differentiation using three‐dimensional cultures that mimic in vivo microenvironments or genetic marker systems to label specific cell types and track their differentiation in vivo . Many different cell models have been used to study differentiation of adipocytes in vitro , with the goal mainly to understand the mechanisms that underlie the development of the lipid droplet and the partitioning of energy to and from it.…”
Section: Adipogenesismentioning
confidence: 99%
“…A first step toward recapitulating BAT in vitro may be to use 3D cultures, which can provide mechanical support, allow physiological cell organization, and prevent loss of mature adipocytes (70). 3D culture techniques are successful for WA culture (71), allowing in vitro culture of unilocular primary mature human WAs (72,73).…”
Section: Culturing Bas In 3dmentioning
confidence: 99%